Photorespiration Enhances Acidification of the Thylakoid Lumen, Reduces the Plastoquinone Pool, and Contributes to the Oxidation of P700 at a Lower Partial Pressure of CO(2) in Wheat Leaves - Wada, Shinya (Plants (Basel), 2020)
The oxidation of P700 in photosystem I (PSI) is a robust mechanism that suppresses the production of reactive oxygen species. We researched the contribution of photorespiration to the oxidation of P700 in wheat leaves. We analyzed the effects of changes in partial pressures of CO(2) and O(2) on photosynthetic parameters. The electron flux in photosynthetic linear electron flow (LEF) exhibited a positive linear relationship with an origin of zero against the dissipation rate (vH(+)) of electrochromic shift (ECS; ΔpH across thylakoid membrane), indicating that cyclic electron flow around PSI did not contribute to H(+) usage in photosynthesis/photorespiration. The vH(+) showed a positive linear relationship with an origin of zero against the H(+) consumption rates in photosynthesis/photorespiration (JgH(+)). These two linear relationships show that the electron flow in LEF is very efficiently coupled with H(+) usage in photosynthesis/photorespiration. Lowering the intercellular partial pressure of CO(2) enhanced the oxidation of P700 with the suppression of LEF. Under photorespiratory conditions, the oxidation of P700 and the reduction of the plastoquinone pool were stimulated with a decrease in JgH(+), compared to non-photorespiratory conditions. These results indicate that the reduction-induced suppression of electron flow (RISE) suppresses the reduction of oxidized P700 in PSI under photorespiratory conditions. Furthermore, under photorespiratory conditions, ECS was larger and H(+) conductance was lower against JgH(+) than those under non-photorespiratory conditions. These results indicate that photorespiration enhances RISE and ΔpH formation by lowering H(+) conductance, both of which contribute to keeping P700 in a highly oxidized state.